One hundred ECMO retrivals before and during the Covid-19 pandemic: an observational study. (April 2023) - Lucchini, Alberto; Gariboldi, Roberto; Villa, Marta; Cannizzo, Luigi; Pegoraro, Flavia; Fumagalli, Letizia; Rona, Roberto; Foti, Giuseppe; Giani, Marco; ,
Abstract: Objectives: Patients with severe acute respiratory distress syndrome may require veno-venous extracorporeal membrane oxygenation (V-V ECMO) support. For patients in peripheral hospitals, retrieval by mobile ECMO teams and transport to high-volume centers is associated with improved outcomes, including the recent COVID-19 pandemic. To enable a safe transport of patients, a specialised ECMO-retrieval program needs to be implemented. However, there is insufficient evidence on how to safely and efficiently perform ECMO retrievals. We report single-centre data from out-of-centre initiations of VV-ECMO before and during the COVID-19 pandemic. Design & setting: Single-centre retrospective study. We include all the retrievals performed by our ECMO centre between January 1st, 2014, and April 30th, 2021. Results: One hundred ECMO missions were performed in the study period, for a median retrieval volume of 13 (IQR: 9–16) missions per year. the cause of the acute respiratory distress syndrome was COVID-19 in 10 patients (10 %). 98 (98 %) patients were retrieved and transported to our ECMO centre. To allow safe transport, 91 of them were cannulated on-site and transported on V-V ECMO. The remaining seven patients were centralised without ECMO, but they were all connected to V-V ECMO in the first 24 hours. No complications occurred during patient transport. The median duration of the ECMO mission was 7 hours (IQR: 6–9, range: 2 – 17). Median duration of ECMO support was 14 days (IQR: 9–24), whereas the ICU stay was 24 days (IQR:18–44). Overall, 73 patients were alive at hospital discharge (74 %). Survival rate was similar in non-COVID-19 and COVID-19 group (73 % vs 80 %, p = 0.549). Conclusion: In this single-centre experience, before and during COVID-19 era, retrieval and ground transportation of ECMO patients was feasible and was not associated with complications. Key factors of an ECMO retrieval program include a careful selection of the transport ambulance, training of a dedicated ECMO mobile team and preparation of specific checklists and standard operating procedures.